Insight into Influenza: A Virus Cap-Snatching - De Vlugt, Corey; Sikora, Dorota; Pelchat, Martin (Université d'Ottawa | University of Ottawa, 2018)
The influenza A virus (IAV) genome consists of eight single-stranded RNA segments. Each segment is associated with a protein complex, with the 3' and 5' ends bound to the RNA-dependent RNA polymerase (RdRp) and the remainder associated with the viral nucleoprotein. During transcription of viral mRNA, this ribonucleoprotein complex steals short, 5'-capped transcripts produced by the cellular DNA dependent RNA polymerase II (RNAPII) and uses them to prime transcription of viral mRNA. Here, we review the current knowledge on the process of IAV cap-snatching and suggest a requirement for RNAPII promoter-proximal pausing for efficient IAV mRNA transcription.
Keywords: cap-snatching; influenza A virus; prime-and-realign; promoter-proximal pausing; Influenza A virus; Protein Binding; RNA Polymerase II; RNA, Messenger; RNA, Viral; RNA-Binding Proteins; Viral Core Proteins; Virus Replication; RNA Caps; Transcription, Genetic